Influence Of Ph And Initial Sludge Concentration On Anaerobic Digestion Of Waste Activated Sludge - Ong, Keat Khim (2007)

(untitled)
Although anaerobic digestion is a common process for treatment of sludge, the digestion rate remains low. Hydrolysis is the first step of anaerobic digestion process and generally is considered to be the rate-limiting step for the overall digestion process. Hence, improvement in the hydrolysis rate is needed to enhance anaerobic digestion of sludge. Chemical hydrolysis can be used as an alternative as it could improve the digestion performance of the sludge. However, hydrolysis process relies on enzymes excreted by the fermentative acidogens, and is strongly pH dependent. Consequently, determination of the optimum pH of sludge digestion is essential and required. In spite of pH, initial concentration of sludge is also an important factor that influences the anaerobic digestion performance of sludge. However, concentrations of total suspended solids (TSS) at a secondary clarifier and a thickener are 1.0% and 4.0% TSS, respectively.This study focuses on a laboratory-scale research on improvement of anaerobic digestion of waste activated sludge (WAS) which was performed by chemical hydrolysis using 0.5 M H2SO4 and 4.0 M NaOH at temperature of 29 ± 1 °C and agitation of 150 rpm. The research was conducted in two phases: the first phase investigated the effect of pH at pH 6.00, 7.00, 8.00, 9.00 and uncontrolled pH on the digestion performance at initial concentration of 4.0% TSS; the second phase investigated and compared the performance of anaerobic digestion at initial concentrations of 1.0% and 4.0% TSS at the optimum pH which was determined from the first phase. Subsequently, determination of kinetic parameters and followed by developments of mathematical models and computer programs were performed at both phases. Significantly higher average removals, removal rates and rate constants of TSS, volatile suspended solids (VSS), total chemical oxygen demand (TCOD) and particulate chemical oxygen demand (PCOD) at controlled pH compared to that at uncontrolled pH. The average removals and removal rates at uncontrolled pH could be improved by 1 to 4 times by controlled pH. Meanwhile rate constants could be improved by 1 to 7. The highest average removal, removal rate and rate constant were found at pH 6.00 followed by pH 8.00, 7.00, 9.00 and uncontrolled pH. The results also indicated that the optimum pH was at pH 6.00. The improvement of sludge digestion was attributed to the enhancement of sludge solubilisation by the chemical hydrolysis as higher soluble chemical oxygen demand (SCOD) concentration was observed at the controlled pH.There was no significant difference in rate constant and removal of the sludge. However, significantly higher average removal rates of TSS, VSS, TCOD and PCOD were achieved at initial concentration of 4.0% TSS. The improvement of the average removal rates of TSS, VSS, TCOD and PCOD was 2.5 to 3.4 times over that at initial concentration of 1.0% TSS giving rise to a higher digestion performance at initial concentration of 4.0% TSS. The experimental results fitted well in first-order models in both phases. High relationships between simulated and experimental results were obtained from both phases experiments with correlation coefficients (R2) ranging from 0.80 to 0.99. Hence, the developed mathematical models can be considered as a useful tool for predicting the concentrations remaining and removals of TSS, VSS, TCOD and PCOD as well as digestion time.